(untitled) (Research, Society and Development, 2022)
Candidiasis is a fungal infection caused by Candida, yeasts that usually colonize the skin and human mucosa. It affects men and women, mainly of childbearing age and the classic treatment involves from the use of antifungal ointments to the choice of the material of the patient’s clothes. The present review aimed to present other studies that provide data on the intervention in the diet of patients with candidiasis, as an ally in the classic treatment of candidiasis and candidiasis by repetition, as well as the use of strains to correct the dysbiotic state and obtain a definitive response to the condition, since the success of the treatment depends on the immunological response and such response is directly linked to the condition of the intestinal microbiota of the individual. For this analysis, searches were made for articles in electronic bases such as PubMed, BIREME and SciELO. The results showed the benefits of a balanced diet, with restriction of carbohydrates, ultra-processed and the benefits of the administration of probiotics such as Lactobacillus and Bifidobacteria.